New Syllabus PRimary Mathematics, Supplementary Reading Material - Dr Foong Pui Yee
New Syllabus Primary Mathematics (NSPM) is a series of textbooks and workbooks specially written to reflect a student-cenetred approach, which engages pupils to have a solid foundation in Mathematics. This series meets the objectives of Pakistan Single National Curriculum 2020. New syllabus Primary Mathematics (NSPM) is a comprehensive series that adopts a spiral design with carefully built-up mathematical concepts and processes. The Concrete-Pictorial-Abstract approach forms an integral part of the learning process through the materials developed for this series. NSPM incorporates the use of concrete aids and manipulatives, use of information and communications technology (ICT), problem-solving, and group work.
Keywords: Textbook Maths -- workbook